Determination of the clinical and prognostic significance of abdominal syndrome in children with syntropic functionnal gastrointestinal disorders - Dzhagiashvili, O. V.; Stoyeva, T. V.; Dragomiretska, O. I. (Journal of Education, Health and Sport, 2018)
The purpose of the study: to analyze the clinical and anamnestic characteristics of the abdominal syndrome with syntropic functional disorders of the digestive system in children and determine its diagnostic and prognostic significance. Materials and methods. A retrospective analysis of medical cases of 649 children with abdominal syndrome aged 1 to 18 years has been conducted. Surgical pathology was diagnosed in 1/3 of children (248 people (38.2 % (95 % CI 34.4÷42.0)). The most children (401; 61.8 % (95 % CI 58.0÷65.6)) after the exclusion of surgical pathology were diagnosed functional disorders of digestive organs, of which syntropic pathology was established in 68.6 % of patients. The leading functional disorder was the irritable bowel syndrome. Results of research. According to the results of univariate logistic regression using the odds ratio, the main clinical features in the differential diagnosis of functional and organic pathology in children with abdominal syndrome were determined, which increased the chance of primary diagnosis of the abdominal pathology at the primary examination of the child before obtaining data from laboratory and hardware examinations. The highest chances of diagnosis of functional disorders of the digestive system were revealed with duration of the disease course up to 2 days (OR 7.9; CI 4.9÷12.6); the presence of abdominal pain of moderate intensity (OR 103.2; CI 58.8÷181.1) without clear localization (OR 7.3; CI 5.1÷10.5); normal body or subfebrile general temperature (OR 29.0; CI 18.2÷46.4); absence of peritoneal irritation (OR 26.7; CI 12.9÷55.6). At the second stage, with the help of binary multivariate logistic regression, a mathematical model with the definition of the quantitative evaluation of each clinical feature and their combination was created, which allowed to conduct a differential diagnosis between functional disorders and intestinal surgical pathology at the stage of the primary care unit with using appropriate coefficients available and probable (Se=95.8 %; Sp=89.1 %; PPV=93.0 %; NPV=94.0 %). Conclusions. The application of the proposed method of multivariate logistic regression, taking into account the integral estimation of the combination of clinical signs, greatly improves the diagnosis of functional intestinal pathology first of all, and allows to rule on the scope of additional examination and curative management by the primary care physician.